Algumas interpelações do Pentecostalismo no Brasil (Some questionings of Pentecostalism in Brazil) - DOI: 10.5752/P.2175-5841.2011v9n22p383 - Oro, Ari Pedro (Horizonte, 2011)
Pentecostalism plays an ever increasing role in Brazilian society specially what concerns its religious field. This article aims to analyse some questionings made on the religious and political spheres by pentecontalism. On the one hand, these questionings aim at the hegemonic role Catholicism plays in the Brazilian religious field as well as its broad religious influence on the political arena and in the mass media. On thinking of itself as having an unique and exclusive religious identity Pentecostalism also questions the very foundations of “the Brazilian catholic culture.” On the other hand, Pentecostalism gives its own interpretation of the Brazilian political field in demarcating its active presence there by practical and symbolic motivations. This does not mean however that pentecostalism desires to get the political power or to challenge the very foundations of the Brazilian republican democracy. Neither does it try to establish an ideological religious hegemony and the submission of the Brazilian citizens to religious dogmas and precepts.